Optimization of Oxidation Temperature for Commercially Pure Titanium to Achieve Improved Corrosion Resistance - Bansal R.; Singh J.K.; Singh V.; Singh D.D.N.; Das P. (My University, 2025)
Thermal oxidation of commercially pure titanium (cp-Ti) was carried out at different temperatures, ranging from 200 to 900 °C to achieve optimum corrosion resistance of the thermally treated surface in simulated body fluid. Scanning electron microscopy, x-ray diffraction, Raman spectroscopy and electrochemical impedance spectroscopy techniques were used to characterize the oxides and assess their protective properties exposed in the test electrolyte. Maximum resistance toward corrosion was observed for samples oxidized at 500 °C. This was attributed to the formation of a composite layer of oxides at this temperature comprising Ti2O3 (titanium sesquioxide), anatase and rutile phases of TiO2 on the surface of cp-Ti. Formation of an intact and pore-free oxide-substrate interface also improved its corrosion resistance. © 2017, ASM International.